Efectos de un entrenamiento pliométrico en extremidades superiores e inferiores en el rendimiento físico en jóvenes tenistas - Pardos-Mainer, E.; Ustero-Pérez, O.; Gonzalo-Skok, O. (Revista Internacional de Ciencias del Deporte, 2017)
The aim of the current study was to assess the effect of plyometric training (upper and lower body exercises) in explosive actions in young tennis players. Twenty-one young tennis players (11 males, 10 females, age 14.33 ± 1.77 years old) participated in the present study and were divided, in a non-randomized manner, into a control group which continued with a regular physical training and in a experimental group, which performed a biweekly plyometric training instead of the habitual fitness training during an 8-week period. Performance variables were assessed through several assessments; a 20-m sprint test (split 5m, 10m and 15m), a 5 + 5 m sprint with a 180º change of direction test, a bilateral (CMJ) and unilateral countermouvement jump test, a maximum distance medicine ball throw test (BM), a speed serve test and a bilateral (SH) and unilateral (SHU) standing broad jump test. Performance`s effect was calculated based on the effect size. All performance variables were improved in both group compared to the pre-test. Furthermore, substantial greater enhancements were obtained in SH, SHU, CMJ and BM in the experimental group in comparison to the control group. Therefore, the plyometric training program might be considered as an effective stimulus to improve explosive actions in young tennis players.